Analysis security system performance MIPv6 in signaling process using AES and Twofish algorithms - Supriyanto Praptodiyono; Fadil Muhammad; Dhandy Wiriyadinata (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
Mobile technology has become a necessity for modern society in the digital era. The ease of various information processes is a driving force for the growth of mobile users. To support continuous connectivity, Mobile IPv6 (MIPv6) is a solution and successor to the current Mobile IPv4 technology. Mobility in accessing a wide range of services is carried out via the Internet, but activities on the Internet make us vulnerable to various malicious acts. Issues such as information security as well as high overheads are a concern for mobile communications. An encryption mechanism is required throughout the signaling phase to construct security associations to enhance MIPv6 security performance. IPsec offers security services at the network layer. There are three encryption algorithms in IPsec, namely DES, 3DES, and AES. The DES algorithm is no longer recommended due to security factors, while AES is still not optimal in wireless networks. This study aims to analyze the performance of the MIPv6 security system and service quality with the AES and Twofish algorithms. Twofish algorithm is a candidate that has the potential for better performance. The experiment concluded that the performance of the Twofish algorithm is superior based on the security of cryptanalysis attacks with a cracking time that is twice as long as AES. In terms of service quality, Throughput Twofish has an increase of 20.05% with a small delay compared to AES, while packet loss is 0.023% for Twofish and 0.077% for AES. Teknologi seluler menjadi kebutuhan masyarakat modern di era digital, kemudahan berbagai proses pengelolaan informasi menjadi pendorong pertumbuhan pengguna seluler. Untuk mendukung konektivitas berlanjut, Mobile IPv6 (MIPv6) menjadi solusi sekaligus penerus teknologi Mobile IPv4 saat ini. Mobilitas akses layanan yang luas dilakukan melalui Internet, namun aktivitas di jaringan Internet membuat kita rentan terhadap berbagai tindakan jahat. Masalah seperti keamanan informasi serta overhead yang tinggi menjadi perhatian komunikasi seluler. Untuk meningkatkan performa keamanan MIPv6, diperlukan metode enkripsi saat proses pensinyalan yang akan membangun asosiasi keamanan. IPsec menawarkan layanan keamanan di lapisan jaringan. Terdapat 3 algoritma enkripsi dalam IPsec, yaitu DES, 3DES, dan AES. Algoritma DES sudah tidak direkomendasikan karena faktor keamanan, sementara AES masih belum optimal dalam jaringan nirkabel. Penelitian ini bertujuan untuk menganalisis performa sistem keamanan dan kualitas layanan MIPv6 dengan algoritma AES dan Twofish. Algoritma Twofish merupakan kandidat yang memiliki potensi performa yang lebih baik. Eksperimen berhasil menyimpulkan bahwa performa algoritma Twofish unggul berdasarkan keamanan serangan kriptoanalisis dengan waktu cracking dua kali lebih lama dibandingkan AES. Dari segi kualitas layanan, Throughput Twofish memiliki kenaikan 20,05% dengan delay yang kecil dibanding AES sementara packet loss masing-masing 0,023% pada Twofish dan 0,077% pada AES.